A Comparative Analysis of Unedited and Published Translation Works in The Pikiran Rakyat Newspaper - Wiwit Sekar Mawarni (Passage, 2017)
This descriptive qualitative study aims at discovering types of translation strategies and changes which occur in a student’s translation works. The data were obtained from a student’s 10 unedited translation works from English to Bahasa Indonesia and 10 published translation works in Bahasa Indonesia. The classification of translation strategies proposed by Vinay and Darbelnet (1958, as cited in Munday, 2001) and Bielsa and Bassnett (2009) is used as a tool for analyzing student’s translation works. The findings reveal 11 types of translating strategies found in student’s unedited translation works. They include borrowing, calque, literal translation, transposition, modulation, equivalence, adaptation, change of title, elimination, addition and summarizing. It reveals that the translator mostly used borrowing among other translation strategies in her unedited translation work from English to Bahasa Indonesia by using Vinay and Darbelnet’s translation strategies. Meanwhile, some changes also occur based on the need of publication and the news agency style.Keywords: translation, translation strategies, unedited and published works